GOYANG PANTAT DALAM TRADISI KEMATIAN: MAKNA SIMBOLIK UPACARA 40 HARI (KADE) DI KAMPUNG TOFOI PAPUA BARAT - Cristophel van Harling; Inet de Lima (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
Funeral rituals are universal cultural expressions that mark the transition between life and death and serve as symbolic spaces imbued with spiritual meaning. In Kampung Tofoi, West Papua, the local community performs a traditional death ritual known as KADE, held on the 40th day after a person's passing. The uniqueness of KADE lies in the practice of “goyang pantat” (hip shaking), a rhythmic, collective body movement functioning both as a means of releasing the soul and facilitating spiritual communication with ancestors. This study aims to analyze the symbolic meaning of this bodily gesture and examine the body’s role as a spiritual agent within the Sumuri belief system. A qualitative-descriptive method was employed, involving participatory observation, in-depth interviews, visual documentation, and literature review. The theoretical framework integrates symbolic anthropology and embodied spirituality, with comparisons to other Indonesian death rituals, including Rambu Solo (Toraja), Tor-Tor Sombah (Batak Toba), and Bolaang Mongondow traditions.The findings reveal that “goyang pantat” is not merely an aesthetic gesture but a profound spiritual medium, a channel for social reconciliation, and a manifestation of communal values. The body in KADE becomes an active transmitter of sacred meaning, bridging the visible and invisible realms. This study highlights the body’s centrality in ritual meaning-making, an area often overlooked in existing scholarship. It underscores the importance of preserving local rituals as dynamic cultural expressions that remain spiritually resonant and socially cohesive in the face of religious pluralism and modernization.